Taxonomical and Anatomical Study of the Species Nonea echioides (L.) Roem. & Sehult (Boraginceae) in Northern Iraq - Al-abide, Naglaa Mustafa (Iraqi Journal of Science, 2021)
The present study deals with some morphological and anatomical characteristics of the Nonea echioides(L.) Roem. & Sehult species belonging to Boraginaceae, which is recorded to have spread recently in Kurdistan region of Iraq.This research focused on some of the important morphological characteristics of the stems, leaves, flowers, and fruits and comparing them with other studies of neighboring countries to Iraq. These morphological characteristics were found to be important in isolating the species of the filed. The anatomical features of the epidermis, stomata, and trichomes were also investigated. The study shows that Nonea echioides belongs to C3 plants based on the anatomical features of the leaf. In conclusion, the present study provided means for field identification and taxonomy of the plant.